2020
DOI: 10.1055/s-0040-1712773
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Calm in the Chaos: An Institutional Protocol for Anesthetic Management of a Patient for Neurosurgery during Coronavirus Disease 2019 Pandemic

Abstract: Abstract“Coronavirus disease 2019” (COVID-19) transmitted by a novel coronavirus via contact or droplet spread is a highly infectious disease, the containment of which requires vigilance and stringent infection control policies. In the backdrop of hospitals becoming hot zones and an increasing number of health care workers contracting the disease, it is crucial to formulate an approach while administering anesthesia during the testing times of COVID-19 pandemic. In this background, this comprehensive article d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 7 publications
0
11
0
12
Order By: Relevance
“…Prior literature on neuroanesthesia and neurosurgery SOPs is available, though limited. [7][8][9][10][11][12] Few authors have evaluated the impact of SOPs in preventing workplace-acquired COVID infection among the HCWs, like done in this study. The incidence of infection among our HCWs was 8.83% in the 5-month period under study, and only sporadic instances were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior literature on neuroanesthesia and neurosurgery SOPs is available, though limited. [7][8][9][10][11][12] Few authors have evaluated the impact of SOPs in preventing workplace-acquired COVID infection among the HCWs, like done in this study. The incidence of infection among our HCWs was 8.83% in the 5-month period under study, and only sporadic instances were found.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A good knowledge of COVID illness and its perioperative implications in neurosurgery, and formulation of workplace protocols that address the safety concerns of HCWs and surgical patients is thus necessary; medical literature including perioperative management guidelines for this novel disease are still limited. [7][8][9][10][11][12] We have devised our own Neurosurgical Standard Operating Procedures (NS-SOPs) for preventing infection transmission among the HCWs, and promptly managing any postoperative COVID-related worsening of neurosurgical patients (►Table 1). We describe here our institutional experience in the perioperative management of neurosurgical patients using these NS-SOPs and present observations from a retrospective study undertaken by us to evaluate, (1) the incidence of workplace-acquired COVID infection among the neurosurgical HCWs and (2) the outcome of neurosurgery done at our hospital during this pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The protocols should have clear workflow guidelines which will help in facilitating multidisciplinary communication to implement effective isolation practices. 1 Ensuring training of healthcare workers regarding donning and doffing of personal protective equipment (PPE) and conducting simulation exercises are essential to ensure compliance to protocol, especially in emergencies like management of neurotrauma. 2 We believe the protocol is well made and may benefit from some modifications in institutions dealing with neurosurgical emergencies and trauma.…”
mentioning
confidence: 99%
“…In this issue, authors from an academic hospital have shared their protocol for anesthetic management of COVID-19 patients for neurosurgery. 1 They have comprehensively discussed the strategies to be adopted by neuroanesthesiologists in the current circumstances. Given the dynamic nature of the disease, new evidence is rapidly emerging to guide the The Ministry of Health and Family Welfare, Government of India, has recently released guidelines on rational use of PPEs by HCPs in preanesthetic evaluation clinics, EDs, OTs, and ICUs in non-COVID areas/hospitals as elective surgeries, which were discontinued amidst the COVID-19 crisis, are likely to restart.…”
mentioning
confidence: 99%
“…In this issue, authors from an academic hospital have shared their protocol for anesthetic management of COVID-19 patients for neurosurgery. 1 They have comprehensively discussed the strategies to be adopted by neuroanesthesiologists in the current circumstances. Given the dynamic nature of the disease, new evidence is rapidly emerging to guide the anesthetic management of surgical patients during the pandemic.…”
mentioning
confidence: 99%